Analysis of platelet count among female athletes of volleyball, judo, and football: a comparative study - Dilpreet Kaur; Arvind Malik; Karuppasamy Govindasamy; Binoy K; Atul Meethal; Tushar Dhar Shukla; Shailesh Kumar; Mou Pramanik; Chandrababu Suresh; Usha Tiwari; Iryna Skrypchenko (H.S. Skovoroda Kharkiv National Pedagogical University, 2022)
Background and Study Aim: Hematological investigation plays a meaningful role in determining the physical standard and performance of the athletes in various games. It is a measure for an athlete's health and physical gesture. The present study portrays the platelet count analysis of university-level female athletes playing volleyball, judo, and football respectively. Material and Methods: 54 female athletes (18 from each game) were selected for the study. The platelet count relationship was the criterion for the present study to differentiate the physical standards of the female players among three different games. To obtain the statistical analysis, one-way ANOVA and posthoc Tukey's HSD test were used to set the significance level of p < 0.05. Results: We found the present results displayed the platelet counts of the players participating in Judo are comparatively higher as compared to football and volleyball. Conclusions: It was observed that there was no correlation between platelet counts between the players participating in three games. No relationship exists between the players from different games concerning their platelet counts. No significant correlation between the three games existed pair-wise individually for comparative statistical analysis as their p > 0.05.